التداولية ومعهود العرب في تلقي الخطاب النبوي: دراسة وصفية تحليلية - جافاكيا، آسية عبد الرحمن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines the relationship between the concept of Pragmatics and Arabic in prophetic discourse and to deliberate the intentions of Prophet's traditions to the addressee. It analyses the customs, rules, writing styles, the use of language in text of situation, semantic elements in structures, relations, and style. The study uses the descriptive and analytical methodology by examining the general meaning of Hadith, analyzing the Hadith in the light of signals elements, and presupposition speech acts. The illocution that confirms when he or she has spoken it, whether as aprevention, promise, question, condolences, and congratulations. This study has shown that the rule of pragmatic elements in the prophet's discourse analysis helps to understand the true meaning of the prophet's speech. The deduction of the concept of using the word is in the following points: the structure of the word as used in the text mode. The study helps to bridge the study of Prophetic discourse in classical period with that of the modern ones.